(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Santri, as future religious and community leaders, still face limitations in their literacy regarding educational and religious policies, despite their strategic role in Indonesia’s civic life. This community service program, conducted at Ihya’ul Ulum DDI Baruga Islamic Boarding School, Majene Regency, aimed to strengthen santri’s policy literacy through a participatory–educative approach. The program integrated socialization, training, mentoring, and evaluation, covering topics such as the relationship between politics and public policy, santri empowerment, and the relevance of policy awareness within the pesantren context. Evaluation results indicated noticeable improvement in santri’s understanding of public policy concepts and their ability to connect policy issues with the pesantren environment. Teachers and students actively participated, provided constructive feedback, and showed strong enthusiasm throughout the activities. These findings highlight the potential of pesantren-based policy literacy initiatives in shaping active, critical, and informed citizens. In the long term, systematic policy support is needed to integrate policy literacy into pesantren curricula and to expand it through collaboration between pesantren, local governments, and academics.